Elevated CO2 Modulates Plant Hydraulic Conductance Through Regulation of PIPs Under Progressive Soil Drying in Tomato Plants - Li, Shenglan; Fang, Liang; Hegelund, Josefine Nymark; Liu, Fulai (Frontiers in Plant Science, 2021)
Increasing atmospheric CO2 concentrations accompanied by abiotic stresses challenge food production worldwide. Elevated CO2 (e[CO2]) affects plant water relations via multiple mechanisms involving abscisic acid (ABA). Here, two tomato (Solanum lycopersicum) genotypes, Ailsa Craig (AC) and its ABA-deficient mutant (flacca), were used to investigate the responses of plant hydraulic conductance to e[CO2] and drought stress. Results showed that e[CO2] decreased transpiration rate (E) increased plant water use efficiency only in AC, whereas it increased daily plant water consumption and osmotic adjustment in both genotypes. Compared to growth at ambient [CO2], AC leaf and root hydraulic conductance (Kleaf and Kroot) decreased at e[CO2], which coincided with the transcriptional regulations of genes of plasma membrane intrinsic proteins (PIPs) and OPEN STOMATA 1 (OST1), and these effects were attenuated in flacca during soil drying. Severe drought stress could override the effects of e[CO2] on plant water relation characteristics. In both genotypes, drought stress resulted in decreased E, Kleaf, and Kroot accompanied by transcriptional responses of PIPs and OST1. However, under conditions combining e[CO2] and drought, some PIPs were not responsive to drought in AC, indicating that e[CO2] might disturb ABA-mediated drought responses. These results provide some new insights into mechanisms of plant hydraulic response to drought stress in a future CO2-enriched environment.